Retrospective Study of Linezolid vs. Daptomycin for the Treatment of Vancomycin--resistant Enterococcal Bloodstream Infection. (4th October 2017) - Rai, Rena; Vaidya, Parth; Desai, Avani; Bhowmick, Tanaya; Weinstein, Melvin; Narayanan, Navaneeth
Abstract: Background: Due to acquired resistance with Enterococcus, antibiotic therapy for vancomycin-resistant enterococcal (VRE) bloodstream infections (BSI) is limited. Current recommendations for the treatment of VRE BSI include either linezolid or daptomycin. The objective of this study was to compare clinical outcomes of VRE BSI in patients treated with linezolid or daptomycin. Methods: This was a retrospective cohort study of inpatients from January 2010 to August 2016 conducted at a large academic medical center. Charts for review were selected based on data from the microbiology laboratory. Adult patients (≥ 18 years old) with VRE BSI treated with linezolid or daptomycin for at least 48 hours were included. Patients treated with linezolid and daptomycin combination therapy or any other antimicrobial agents were excluded. The primary outcome measure was 14-day in-hospital mortality. Secondary outcomes included time to blood culture clearance, microbiologic failure, antibiotic failure, and BSI relapse. A multivariable logistic regression model was performed to adjust for potential confounders. Results: There were a total of 93 patients, 62 treated with linezolid and 31 with daptomycin. Median daptomycin dose was 6.14 mg/kg (IQR, 5.98-6.71). Outcome of 14-day in-hospital mortality was not significantly different for patients treated with linezolid and daptomycin (17.7% vs. 29%, P = 0.21, respectively). Median time to blood culture clearance was not significantly different for linezolid vs. daptomycin therapy (3.0 days vs. 3.7 days, P = 0.78, respectively). All other secondary outcomes were not significantly different between treatment groups. Multivariate logistic regression analysis indicated 14-day in-hospital mortality was independently associated with Pitt bacteremia score (adjusted OR 1.48, 95% CI: 1.12-1.97) but showed no significant association with daptomycin treatment (adjusted OR 1.54, 95% CI: 0.46-5.14). Conclusion: There were no significant differences in clinical outcomes for patients treated with linezolid or daptomycin for the treatment of VRE BSI. Additional prospective studies with larger sample sizes are needed to further validate these conclusions. Role of daptomycin dose on outcomes requires further study. Disclosures: All authors: No reported disclosures.